Cytotoxic effects of colicins E1 and E3 on v-myb-transformed chicken monoblasts - Smarda, J; Fialová, M; Smarda, J (Folia biologica, 2001)
Colicins show a considerable cytostatic activity, which is much less known and understood than their killing activity targeting bacteria of the Enterobacteriaceae family. In this communication, the cytotoxic effects of colicins E1 and E3 on v-myb-transformed chicken monoblasts BM2 are presented. We detected clear reduction of the viable cell number induced by colicins E1 and E3, occurring without apparent changes in cell cycle profiles. The level of inhibition was proportional to the colicin concentration within the limits of 0.5-1.25 microg/ml. This result documents that colicins produced by Enterobacteriaceae exert their cytotoxic effects on leukemic cells.
Keywords: Cell Survival; koliciny; protinádorové látky; Cell Line, Transformed; Colicins; Antineoplastic Agents; Cell Division; kur domácí; Animals; Oncogene Proteins v-myb; onkogenní proteiny v-myb; Chickens; buněčný cyklus; transformované buněčné linie; Cell Cycle; viabilita buněk; zvířata; buněčné dělení